2009
DOI: 10.1002/art.24655
|View full text |Cite
|
Sign up to set email alerts
|

Association of adrenergic receptor gene polymorphisms with different fibromyalgia syndrome domains

Abstract: Objective. Fibromyalgia (FM) patients have signs of relentless sympathetic hyperactivity associated with hyporeactivity to stress. Adrenergic receptors (ARs) are parts of the sympathetic nervous system that are fundamental for maintenance of homeostasis. We undertook this study to correlate ␣-AR and ␤-AR gene polymorphisms with the presence of FM and with different domains of the FM syndrome as measured by the Fibromyalgia Impact Questionnaire (FIQ).Methods. We studied 78 Mexican FM patients and 48 age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 14 publications
3
59
1
3
Order By: Relevance
“…Significant familial aggregation, convincing demonstrations of genetic linkages and associations demonstrate an underlying genetic basis for fibromyalgia [5]. Many studies have examined the potential contribution of the candidate gene polymorphisms to fibromyalgia susceptibility, but these studies have produced diverse results [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Significant familial aggregation, convincing demonstrations of genetic linkages and associations demonstrate an underlying genetic basis for fibromyalgia [5]. Many studies have examined the potential contribution of the candidate gene polymorphisms to fibromyalgia susceptibility, but these studies have produced diverse results [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that CBP is a potent inhibitor of 5-HT2a and the adrenergic a-2 receptors -A, -B, and -C 37 . Genetic linkages have associated FM with genes encoding 5-HT2a and adrenergic receptors 38,39 . In addition, ritanserin, another 5-HT2a receptor inhibitor, provided benefit to the sleep quality but not to pain or tenderness of patients with FM 40 .…”
Section: Discussionmentioning
confidence: 99%
“…also included in our study as well as polymorphisms at adrenergic receptor genes, 23 and special immunogenetics leading to a proinflammatory status, [16][17][18]34 among others as CYP450 enzymatic polymorphisms which are mainly related to the pain management. [35][36][37][38] All these genes are involved in the neurotransmitters balance determining the potential to have excess or defect in any of them.…”
Section: 22mentioning
confidence: 99%